2008
DOI: 10.1007/s00436-008-1165-3
|View full text |Cite
|
Sign up to set email alerts
|

Skin-scale genetic structure of Sarcoptes scabiei populations from individual hosts: empirical evidence from Iberian ibex-derived mites

Abstract: The objective of the present study was to examine the extent of genetic diversity among Sarcoptes scabiei individuals belonging to different skin subunits of the body from individual mangy hosts. showing the proportion of shared alleles between pairs of individual mites representing three skin subpopulations (head, back, and abdomen subunits), allowed the clustering of some mite samples up to their skin subunits. This genetic diversity of S. scabiei at skin-scale did not have the same pattern in all considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…The skin-scale genetic pattern has been observed previously in S. scabiei isolated from head, abdomen and back of Iberian ibexes suggesting a local colonization dynamics after a single infestation or as the result of repeated (Alasaad et al 2008). Nevertheless, this fact needs to be tested.…”
Section: Discussionmentioning
confidence: 82%
“…The skin-scale genetic pattern has been observed previously in S. scabiei isolated from head, abdomen and back of Iberian ibexes suggesting a local colonization dynamics after a single infestation or as the result of repeated (Alasaad et al 2008). Nevertheless, this fact needs to be tested.…”
Section: Discussionmentioning
confidence: 82%
“…Also, microsatellite markers were used by Alasaad et al (2008a) to describe a new phenomenon of genetic structuring among S. scabiei at individual host skinscale level. On the other hand, Zahler et al (1999) analysed 23 pooled samples of mite isolates (not single mites) from nine host species in four continents, using the second internal transcribed spacer (ITS-2) of ribosomal DNA (rDNA) as genetic marker, and concluded that Sarcoptes consists of a single, heterogeneous species.…”
Section: Introductionmentioning
confidence: 99%
“…As described by Alasaad et al (2008), nine specific microsatellites (Sarms 33,34,(36)(37)(38)40,41,44,and 45) of Sarcoptes mites were amplified with multiplex PCR. One primer from each set was 5 labeled with 6-FAM, VIC, NED, or PET ® fluorescent dye tag (Applied Biosystems, Foster City, CA, USA).…”
Section: Dna Extraction and Fluorescent-based Pcr Analysis Of Microsamentioning
confidence: 99%